(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
The given article deals with the abbreviations which are commonly used in educational sphere. Abbreviations are widely used in the educational sphere to facilitate communication and save time and space when writing or speaking about various topics. These abbreviations are commonly found in academic settings, research papers, textbooks, and educational materials to convey information efficiently. It is essential to be familiar with these abbreviations when working in the field of education to communicate effectively with colleagues and students.